Succinic semialdehyde dehydrogenase deficiency: in vitro and in silico characterization of a novel pathogenic missense variant and analysis of the mutational spectrum of ALDH5A1 - Brennenstuhl, Heiko; Didiášová, Miroslava; Assmann, Birgit; Bertoldi, Mariarita; Molla, Gianluca; Jung-Klawitter, Sabine; Kuseyri Hübschmann, Oya; Schröter, Julian; Opladen, Thomas; Tikkanen, Ritva (International journal of molecular sciences, 2020)
Succinic semialdehyde dehydrogenase deficiency (SSADHD) is a rare, monogenic disorder affecting the degradation of the main inhibitory neurotransmitter γ-amino butyric acid (GABA). Pathogenic variants in the ALDH5A1 gene that cause an enzymatic dysfunction of succinic semialdehyde dehydrogenase (SSADH) lead to an accumulation of potentially toxic metabolites, including γ-hydroxybutyrate (GHB). Here, we present a patient with a severe phenotype of SSADHD caused by a novel genetic variant c.728T > C that leads to an exchange of leucine to proline at residue 243, located within the highly conserved nicotinamide adenine dinucleotide (NAD)+ binding domain of SSADH. Proline harbors a pyrrolidine within its side chain known for its conformational rigidity and disruption of protein secondary structures. We investigate the effect of this novel variant in vivo, in vitro, and in silico. We furthermore examine the mutational spectrum of all previously described disease-causing variants and computationally assess all biologically possible missense variants of ALDH5A1 to identify mutational hotspots.
Gesehen am 02.02.2021